Sons or Daughters? The Impact of Children's Migration on the Health and Well-Being of Parents Left Behind - Jackline Wahba; Chuhong Wang (Institute of Labor Economics (IZA), 2019)
We study the impact of adult children's internal migration on the health and subjective well-being of elderly parents left behind, distinguishing between the gender of the migrant children. To overcome migration endogeneity, we exploit novel and exogenous variation in children's astrological characteristics and apply instrumental variables methods. We find a positive effect of the migration of daughters on parents' health and life satisfaction, but no such beneficial effects when sons migrate. We further explore the mechanism through which this gender-biased migration effect may arise. Our findings have important implications for regions and countries that have high rates of female emigration.
Keywords: O15; I12; J14; J16; R23; 330; migration; health; subjective well-being; gender; Chinese zodiac signs